The Effects of a Dietary Promotion Program on Nutritional Status, Knowledge, Albumin Levels, and Total Iron-Binding Capacity in Hemodialysis Patients - Saelim, Rattanaporn; Nangam, Thanida; Onputta, Sasimaporn; Jangjaroenphorn, Itsara (Journal of health and health management, 2025)
This study is a quasi-experimental research design employing a one-group pretest-posttest approach. The aim of the study was to evaluate the level of knowledge, nutritional status, albumin levels, and iron-binding capacity before and after the implementation of knowledge promotion and dietary selection guidelines. A sample of 30 participants was Chronic kidney disease patients receiving hemodialysis who received hemodialysis services at the Tropical Medicine Hospital, Bangkok, between October 2022 and March 2023 and selected using purposive sampling based on predetermined criteria. The research instruments included: 1) a personal information questionnaire, 2) a knowledge questionnaire, 3) a nutritional status assessment tool, and 4) a knowledge promotion and dietary guidelines plan. Data analysis was performed using descriptive statistics, including percentages, means, standard deviations, and paired t-tests for comparison.The results indicated that, following the knowledge promotion and dietary selection guidelines: 1) the sample group exhibited a statistically significant increase in knowledge regarding nutrition for patients with chronic kidney disease undergoing hemodialysis (p < .001), 2) the sample group showed a statistically significant improvement in nutritional status (p < .001), 3) the sample group showed a statistically significant increase in blood albumin levels (p < .001). However, there was no statistically significant difference observed in the iron-binding capacity. The findings of this study suggest that promoting knowledge and providing dietary guidelines can significantly improve knowledge, nutritional status, and albumin levels in patients with chronic kidney disease undergoing hemodialysis. However, this intervention did not show an effect on the iron-binding capacity.